Comparison of Lung Functions Among Asthmatic Children in Malaysia - Hashim, Zailina; Jalaluddin, Juliana; Hashim, Jamal H. (Universiti Putra Malaysia Press, 2004)
A comparative study was conducted on 163 asthmatic children from Kuala Lumpur (polluted area) and 38 asthmatic children from Terengganu (less polluted area). The objective of this study was to compare the lung functions of the asthmatic children between the 2 sexes and study areas. Questionnaires and diary cards were used to obtain background information and frequency of asthma attacks. A spirometer was used to measure lung functions of the asthmatic children. Findings showed that there was a significant difference in the FEV,% predicted (p=0.002), FEV/FVC % predicted (p =0.001) and the